Remote teaching and learning: a bibliometric analysis - Ahmad @ Abdul Mutalib, Hawa; Ahmad, Shamsatun Nahar; Zakaria, Nadisah; Foo, Siong Min (2023)
Purpose- This study examines trends in the publication of remote teaching and learning (RTL) research by year, universities, nations, topic matters, and keywords. Design/methodology/approach- Using the keywords "remote teaching and learning," "remote learning," or "remote teaching," the data was extracted from the Scopus database. The final dataset used for analysis is 1,748. Three techniques were used to examine the dataset: performance analysis using the Scopus analyzer; science mapping based on citation, co-authorship, and co-word, and network analysis through visualization with the VOSviewer programme. Findings- The findings reveal that RTL research publications contribute the most in 2022. The top-cited document is by Mukhtar et al. (2020). The most active and highest number of publications in RTL is Fuchs, K. COVID-19 and emergency remote teaching are identified as the top two authors’ keywords. Monash University, Pennsylvania State University, and University College London are the top three universities. The United States of America is the most active country, followed by the United Kingdom and Australia. Social Sciences, Computer Science, and Medicine are the subject areas that have the most publications. Journal of Chemical Education is the most represented journal, followed by the Journal of Chemical Education, Education Sciences, and Sustainability (Switzerland). Research limitation- This study used the keywords "remote teaching", "remote learning", and "remote teaching" from the Scopus database, and the method used was only descriptive analysis to understand the trends of publication. Originality/value- This study gives an overview of the remote teaching and learning studies that provide a preliminary idea for the researcher on what has been researched. It is helpful, particularly to young scholars.